Prognostic Factors for Absence Epilepsy in Childhood - So Young Kang; Chung Mo Koo; Se Hee Kim; Heung Dong Kim; Joon Soo Lee; Hoon-Chul Kang (Korean Child Neurology Society, 2019)
Purpose Childhood absence epilepsy (CAE) is a common form of idiopathic generalized epilepsy with onset middle childhood and has typically a good prognosis, but remission rates vary. We aimed to analyze unfavorable prognostic factors in children initially diagnosed with CAE. Methods We retrospectively reviewed 48 patients under 13 years of age who were diagnosed with CAE at the Severance Children's Hospital, Seoul, Korea. We analyzed clinical information including comorbidity through neuropsychological test. Results Thirteen of the 48 patients (27%) showed an unfavorable prognosis, with clinical seizures or seizure waves on electroencephalogram persistent even after 12 months of anticonvulsant therapy. The mean age at absence seizure onset was 6.51±2.36 years. The most commonly used antiepileptic drug (AED) was ethosuximide, and the median duration of initial AEDs was 25.63±24.41 months. The presence of comorbidity and clinical absence seizures after 6 months of AEDs correlated with an unfavorable prognosis. Motor seizures were the most unfavorable prognostic factor during follow-up. Conclusion This study shows that clinical absence seizures after 6 months of AED, comorbidity, and motor seizure are the most important predictive factors of an unfavorable prognosis for absence epilepsy in childhood. This study suggests that when these factors are observed, early intervention needs to be considered.